Effects of a statewide protocol for the management of peritoneal dialysis-related peritonitis on microbial profiles and antimicrobial susceptibilities: A retrospective five-year review - McGuire, A.; Carson, C.; Inglis, T.; Chakera, Aron (2015)
Background: Peritonitis is a major complication of peritoneal dialysis (PD) and is associated with significant morbidity and mortality. Early empirical antibiotic therapy is recommended, with the choice of agents guided by local resistance patterns. As routine use of specific antimicrobial agents can drive resistance, regular assessment of causative organisms and their susceptibility to empirical therapy is essential. Methods: We conducted a retrospective review of all PD peritonitis cases and positive PD fluid cultures obtained over a 5-year period in Western Australia following the introduction of a statewide protocol for the initial management of PD peritonitis with intraperitoneal vancomycin and gentamicin. Results: The incidence of PD peritonitis decreased from 1 in 16 patient months (0.75/year at risk) to 1 in 29 patient months (0.41/year at risk) over the 5 years. There were 1,319 culture-positive samples and 1,069 unique isolates identified. Gram-positive bacteria accounted for 69.9% of positive cultures, with vancomycin resistance averaging 2% over the study period. Gram-negative bacteria accounted for 25.4% of positive cultures, with gentamicin resistance identified in an average of 8% of organisms. No increase in antimicrobial resistance to vancomycin or gentamicin occurred over the 5 years and there was no change in the proportion of gram-positive (69.9%), gram-negative (25.4%) or fungal (4.4%) organisms causing PD peritonitis. Conclusions: Over time, the peritonitis rates have dramatically improved although the profile of causative organisms remains similar. Empirical treatment of PD peritonitis with intraperitoneal vancomycin and gentamicin remains efficacious, with high levels of susceptibility and no evidence that the introduction of this statewide empirical PD peritonitis treatment protocol is driving resistance to these agents.